2019
DOI: 10.1177/0144598719889661
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of building-integrated photovoltaics based on perovskite single junction and perovskite/silicon tandem solar cells

Abstract: Considering the perovskite-based building-integrated photovoltaics, we use the single box model of 4 × 4 × 3 m3 to illustrate a promising solution for the zero-energy residential building and the distributed power generators in the Wuhan urban area in China (N30° E114°), where we have the high ratio of façades on the tall buildings. According to our estimation, the energy gains from the solar cells on the façades could be competitive with the ones on the rooftops. In comparison with the perovskite/silicon tand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The model was validated using recorded experimental data over an entire year. Recently, Gong et al (2019) used the single box model of 4 × 4 × 3 m 3 which converted 35% solar radiation to electricity is a promising solution for distributed power generation and the zero-energy residential building in the Wuhan urban area in China [231].…”
Section: Future Of Pscs Based Bipvmentioning
confidence: 99%
“…The model was validated using recorded experimental data over an entire year. Recently, Gong et al (2019) used the single box model of 4 × 4 × 3 m 3 which converted 35% solar radiation to electricity is a promising solution for distributed power generation and the zero-energy residential building in the Wuhan urban area in China [231].…”
Section: Future Of Pscs Based Bipvmentioning
confidence: 99%
“…Through computer simulation under the TRNSYS environment, it was predicted that 35.2% of the total energy was provided by solar energy. Gong et al. (2020) developed a single box model to evaluate the energy performance of perovskite-based building-integrated photovoltaics.…”
Section: Research Topics Investigatedmentioning
confidence: 99%
“…Through computer simulation under the TRNSYS environment, it was predicted that 35.2% of the total energy was provided by solar energy. Gong et al (2020) developed a single box model to evaluate the energy performance of perovskite-based building-integrated photovoltaics. Simulation results showed that a single box could achieve zero energy demand except for January and December while maintaining the indoor air temperature at 18 C in winter and less than 26 C in summer.…”
Section: Energy Savings Through Renewable Energy Usagementioning
confidence: 99%
“…With the advancement of science and technology, solar energy is becoming more and more economically viable [9]. Photovoltaic (PV) systems are considered as one of the most promising propitious items to exploit the received energy from the sun [10].…”
Section: Introduction 1motivationmentioning
confidence: 99%